Pelatihan Pijat Oksitosin Pada Keluarga Ibu Nifas Di RSUP Dr. Soeradji Tirtonegoro Klaten - Paryono Paryono (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Training Of Oxytocin Massage, Postpartum Family. Training is a a shortterm investment to help improve a person's ability to perform his/ her duties. The oxytocin massage can be done by the nearest person or post partum family. Tthe lack knowledge on postpartum family about oxytocin massage causes the need for information about the oxytocin massage. In order for information about oxytocin massage is more easily delivered then the business of oxytocin massage training to the post partum family. If the postpartum family can do the oxytocin massage, the milk production (ASI) becomes smooth and the baby gets enough breast milk. Goal this research was to know the difference of oxytocin massage skills before and after being trained in the postpartum family in dr. Soeradji Tirtonegoro Klaten hospital. The research type is quasi experiment with one group pretest-posttest research design. The population in this study is the postpartum family in Melati I room dr. Soeradji Tirtonegoro Klaten hospital. Samples taken are the postpartum families who was given the training of oxytocin massage is 30 people. Data collection was done by intervening in oxytocin massage training and observation. Data were analyzed univariant with central tendency and bivariant analysis with Paired Sample t-test. Univariant analysis showed that the average score of oxytocin massage skills in the postpartum family before training 2.2 + 4.65 and the average score of oxytocin massage skills in the postpartum family after receiving training 16.6 + 0.49. The bivariant analysis hows that the value of t test -17.124 (-17.124> -2.045 <2.045). It proves that Ho is rejected and Ha accepted which means there is a difference in oxytocin massage kills before and after being trained in the postpartum family in dr. Soeradji Tirtonegoro Klaten hospital.